The Saudi-Italian-French Archaeological Mission at Dūmat al-Jandal (ancient Adumatu). A first relative chronological sequence for Dūmat al-Jandal. Architecture and pottery - Loreto, Romolo (Proceedings of the Seminar for Arabian Studies, 2012)
A second archaeological campaign was carried out at Dūmat al-Jandal between October and November 2010 by the new Saudi-Italian-French Archaeological Mission in Saudi Arabia. As the work developed it became possible to define a first relative chronological sequence for Dūmat al-Jandal (ancient Adumatu according to the Assyrian texts) because of the stratigraphie relationships between architectonic structures, the architectonic masonry of the excavated buildings, and the ceramic items that were discovered in situ. We were able to define different phases of the Islamic occupation of the site and a late pre-Islamic phase related to a massive structure (Building A), which we were able to identify as a pre-Islamic building (late Nabataean/Roman-Byzantine) due to the construction techniques and the pottery items found within it. A sounding carried out inside Building A allowed us to reach its foundation layers, which were made of more ancient materials (including fine Nabataean pottery and sigillata orientale potsherds) dating back to the first century AD. These enabled us to distinguish a first Nabataean occupation for Dūmat al-Jandal. The pottery remains in situ gave us the opportunity to study trade contacts between the al-Jawf oasis and the surrounding regions (north-west Arabia and the Gulf region) during the first centuries AD.